Association of angiotensin converting enzyme gene polymorphism among overweight hypertensive patients attending Murtala Muhammad Specialist Hospital, Kano State, Nigeria - ALI GAMBO, MUHAMMAD; Hassan, Abdullahi Musa; Bindawa, Sani Yusuf (World Nutrition, 2025)
One risk factor for high blood pressure is obesity. An enzyme called the angiotensin-converting enzyme (ACE) is responsible for vasoconstriction. It is possible that ACE gene insertion or deletion polymorphisms are linked to hypertension. The goal of this investigation is to identify a correlation between blood pressure and polymorphisms in the ACE gene in obese patients. This study employed a cross-sectional design and an analytical observational approach. To investigate ACE gene polymorphism, blood samples were collected from 40 overweight patients. The Kruskal-Wallis test was employed to examine the correlation hypothesis. The findings indicated that type II (62.5%), type ID (25%), and type DD (12.5%) ACE gene polymorphisms were the most prevalent; the mean systolic blood pressure values for type II were 129.5 mmHg, type ID was 142.3 mmHg, and DD was 164.9 mmHg. Diastolic pressure was 90.5 mmHg on average for ACE gene polymorphism type II, 101.4mmHg on average for type ID, and 113.9 mmHg on average for type DD. There was a correlation between the angiotensin ACE gene polymorphism and systolic pressure at p=0.002 and the diastolic pressure at p=0.004. There was a correlation between ACE gene polymorphism and BMI at p= 0.004, waist circumference at p= 0.001, body adiposity index at p= 0.003, and mid-upper-arm circumference at p= 0.006. Thus, we concluded that there is a relationship between blood pressure, degree of obesity, as measured by anthropometric indices, and polymorphism in obese, hypertensive patients.